SALMAN MUMTAZ’S LITERATURE-STUDY ACTIVITY - Gadim , I. (EurasianUnionScientists, 2021)
The article is devoted to Salman Mumtaz, who played an exceptional role in the development of Azerbaijani literature. It is emphasized here that Salman Mumtaz spent his childhood in Ashgabat, but he lived the next part of his life in the native country Azerbaijan. Knowing a number of Eastern, including Turkish and Russian languages perfectly Salman had shown interest in the reading of world literature. This enthusiasm pushed him to research-study gradually. Although his first published research work was related to Persian literature, he later showed interest in the study of Azerbaijani literature.